(3EagGe GdCagGe eYGfi YbjOI TjN GdESdGe (B( (3GdYR Hf YHO GdSdGe(B)s - (3hdi GdOjf eMeO Hf CMeO GdOjHGLis; (3YR GdOjf YHO GdYRjR Hf YHO GdSdGe Hf CHh GdbGSe Hf GdMSf GdSdej GdOeTbj, GdYR Hf YHO GdSdGe,J (B660 (3g` s ((3GdeOQSI GdefUhQjI HGdbGgQI s)
(3ChdgG (B:s
(3GdMeO ddg aQTO GdYbhd hGdCagGe hHYO abhd TjN GdESdGe ajeG CedGg ef bhGYO GdYbGFO GYde Edi BNQg eQJH Ydi ebOeI hegeGJ hJJeI s
(3BNQgG (B:s
(3hKGfjgeG Cf PcQi eG PcQJg ef BjGJ GdbQBf GdeLjO hef GdCSeGA GdMSfi hef GdCMGOjK GdfHhjI GJeg GdOjf hYdeG GdeSdejf hYfOc GdbQBf hGdSfI JeJ gPg GdfSNI s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B21s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds